25-Hydroxycholesterol induces both P2X7-dependent pyroptosis and caspase-dependent apoptosis in human skin model: New insights into degenerative pathways. (October 2017) - Olivier, Elodie; Dutot, Mélody; Regazzetti, Anne; Laprévote, Olivier; Rat, Patrice
Graphical abstract: Highlights: 25-OH induces caspases 8 and 3 activation and chromatin condensation in human keratinocytes. 25-OH activates P2X7 receptor, along with an increase in caspase-1 and proinflammatory cytokines release. 25-OH is a key actor in skin degeneration process. Abstract: Degenerative diseases are characterized by both cell death and inflammation, which involve different pathways such as apoptosis and pyroptosis. Oxysterols, oxidized derivatives of cholesterol, are known to act as key actors in degenerative disorders such as skin photoaging. We hypothesize that oxysterols could be implicated in either apoptosis or pyroptosis, or both. The aim of our study was first to quantify oxysterol levels in keratinocytes as a function of aging and UV irradiation. Second, we evaluated the effects of 25-OH oxysterol on apoptosis and pyroptosis hallmarks in keratinocytes. Our results showed that 25-OH exhibited an increasing after UV irradiation, highlighting the pivotal role of this oxysterol in skin degeneration. In our model, 25-OH induced not only caspases-dependent apoptosis associated to granzyme B release but also P2X7 receptor-dependent pyroptosis in skin cells. 25-OH seems to be at the origin of the main toxic pathways responsible for degenerative disorders; therefore, it could be the target of antidegenerative treatments, opening new potential therapeutic strategies.